A aplicação da gestão por competências nos processos de gestão de pessoas: um estudo com os servidores técnico-administrativos no Centro de Ciências Jurídicas e Sociais/UFCG. - SOUSA, Maria Guesnadia Teodoro de Oliveira. (2018)
In the Brazilian Public Administration, the model of people management by competences was introduced by means of Decree n. 5.707 / 2006, which established the Personnel Development National Policy with the aim, among other things, of improving the efficiency, effectiveness and quality of public services provided to society and the permanent development of public servants. In this context, the objective of this study is to analyze how the application of the competency based management model in the people management processes is experienced by the technical administrative staff of the Center for Legal and Social Sciences (CCJS) at the Federal University of Campina Grande (UFCG). The research is characterized as a case study, with qualitative approach and it is classified as exploratory descriptive and as a field study. In the data collection, 16 interviews with servers and documentary consultation were carried out. Content analysis subsidized the data analysis procedure. The main results of the research in the five people management processes were as follows: with regard to the supply it was noticed that, without proper planning of the workforce, there is a risk of server aggregation failures at the Center characterized by the lack of servers or due to the lack of profile for the good performance of the assignments; about the application, can be said that the way that UFCG and CCJS receive the new servers and integrate them into their culture and context does not meet the expectations of these servers; with regard to compensation, it was noticed that there is an effort by the institution and the Center to carry out some actions to retain its employees, seeking to ensure a more pleasant and safe environment, but it must be considered that the institution can invest more and better in life quality programs; with regard to development, it has been proven that one of the institution's goals is the training of its technical administrative staff, but this institutional policy needs to be more effective, through a training and continuous qualification program, in order to meet institutional needs; with respect to monitoring, related to monitoring, it has been found that a talent pool is a competency management tool that can be used by the CCJS to properly allocate the workforce, and that the annual functional performance assessments do not reflect the actual performance of the evaluated servers in the Center. The research conclusions demonstrated that the competency based people management system has a gap between what is recommended in the literature, the provisions in legislation and what is practiced in the people management at UFCG, specifically at CCJS. The management by competences is viable in the Brazilian Public Administration, but depends on adjustments necessary to the specificities of the public sector.